Solution:
Given the graphs of f(x) and g(x) below:
The point where f(x)=g(x) is the point where the graph of f(x) cuts the graph of g(x).
Thus, the graphs cut each other at (0, 4) and (-4, 4).
This implies that
![\begin{gathered} For\text{ the graph f\lparen x\rparen,} \\ f(-4)=4 \\ f(0)=4 \\ For\text{ the graph g\lparen x\rparen,} \\ g(-4)=4 \\ g(0)=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/re4yrpbmjn8dxq7om4qtriubcaiazax2aq.png)
Hence, we can conclude that f(x) = g(x) is represent
![\begin{gathered} f(-4)=g(-4) \\ and \\ f(0)=g(0) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/b7bbropwvcylzmu7k5o86by30lv4vkg6jq.png)
The correct option is